Shariah-Compliant Housing: Opportunities and Challenges in Modern Markets - Noorsidi Aizuddin Mat Noor; Farhana Diana Deris; Mustafa Omar; Hamdi Abdul Hamid; Afizan Mokhtar (Indonesian Journal of Islamization Studies, 2024)
This study examines the market potential and challenges of Shariah-compliant housing, a niche in real estate adhering to Islamic principles against interest, gambling, and excessive uncertainty. Given the rising global Muslim population and demand for Islamic products, this research is timely. Focusing on Malaysia, the study employs a mixed-method approach, utilizing quantitative surveys of 150 Muslim respondents and qualitative interviews with industry experts. Findings indicate a strong preference for Shariah-compliant housing, with 78% willing to pay a premium, yet barriers like limited awareness and inadequate financing persist. The study emphasizes the need for education and improved regulations to foster market growth.